Pendampingan Optimalisasi Pekarangan Dengan Konsep Smart Agriculture - Alia Bihrajihant Raya; Mesalia Kriska; Dody Kastono; Nurul Trya Wulandari; M. Puji Tri Septijono; Valentina Dwi Suci Handayani; Agus Dwi Nugroho (Jurnal Pengabdian dan Pengembangan Masyarakat, 2020)
The main problems of the community in the Poncosari Village are they do not know how to optimally the local potentials and do not know the development of information technology. The aims of this activity are to optimize the potential of the garden in Poncosari Village for agricultural activities and the empowerment of farmer women groups in Poncosari Village in managing smart agriculture. This activity was carried out in Poncosari Village, Srandakan Subdistrict, Bantul Regency in March until August 2019. The method used was a Focus Group Discussion, counseling, training and assistance, demonstration plot, and evaluation and monitoring. The results of this activity show that most people have started to cultivate their gardens with vegetables. The Poncosari Village community also began to recognize and actively use the Desa Apps to consult farming and marketing issues.